Perbandingan Efektivitas Daya Hambat Antibakteri Ekstrak Rimpang Jahe Merah (Zingiber officinale var rubrum) dengan Formula Obat Kumur Lidah Buaya Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Nadia Amatul Khayum; Rima Semiarti; Nelvi Yohana (Faculty of Dentistry Universitas Andalas, 2019)
Red Ginger extract and Aloe vera mouthwash formulae have an antibacterial properties. The Red Ginger extract contains of gingerol, essential oil, terpenoid, fenol, flavonoid, and the Aloe vera mouthwash formulae contains of aloe berbadensis. This compound can be used in inhibition against the growth of Staphylococcus aureus that cause infections. The method of this research is a laboratory experimental. The Red Ginger extract prepared by maceration method with 96% ethanol solvent. The Aloe vera mouthwash formulae is the ready stock. Discs soaked into two groups solution for 15 minutes, then placed on MHA media contain Staphylococcus aureus to see the inhibition power. The result showed that the Red Ginger extract and Aloe vera mouthwash formulae show the inhibiting power with a strong category. The average diameter inhibiting power of Red Ginger extract is 10,75 mm and Aloe vera mouthwash formulae is 12,82 mm. Independent Sample T-test showed the significance value is 0,00 (p<0,05). The conclusion of this reasearch is that the Aloe vera mouthwash formulae is more effective than Red Ginger extract in inhibiting the growth of Staphylococcus aureus.